2002
DOI: 10.1007/s00417-002-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring retinal function in neovascular maculopathy using multifocal electroretinography – early and long-term correlation with clinical findings

Abstract: Objective monitoring of retinal function and correlation with morphological and psychophysical findings was at least in part possible in patients suffering from AMD and myopia. In all of four patients whose subfoveal CNV was documented by fluorescein angiography. Response densities were reduced particularly in the central 5 degrees and in visual acuity. The mfERG data showed a moderate to high statistical correlation with visual function as measured by visual acuity. On the other hand, the greatest linear dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
3
33
1
Order By: Relevance
“…14,54,56,57,72,91,110,122,151,152,167,172,228,248,258 Patients with early AMD were found to have significant reduction in the foveal P1 amplitude and delay in N1 implicit time compared with normal age-matched controls. 167 The extent of mfERG changes is influenced by the severity of AMD as patients with neovascular AMD had more severe reductions in mfERG response amplitudes and delays in implicit times compared with patients with dry AMD.…”
Section: Clinical Applications Of Mferg In Acquired Retinal Diseases mentioning
confidence: 96%
“…14,54,56,57,72,91,110,122,151,152,167,172,228,248,258 Patients with early AMD were found to have significant reduction in the foveal P1 amplitude and delay in N1 implicit time compared with normal age-matched controls. 167 The extent of mfERG changes is influenced by the severity of AMD as patients with neovascular AMD had more severe reductions in mfERG response amplitudes and delays in implicit times compared with patients with dry AMD.…”
Section: Clinical Applications Of Mferg In Acquired Retinal Diseases mentioning
confidence: 96%
“…Controversy exists as to the spatial resolution of the mfERG measurements in AMD patients and its capacity to accurately reflect morphological alterations in the posterior pole by a changed functional readout. Gerth et al [13] and Jurklies et al [14] found a weak correlation between mfERG response and the linear dimension of drusen or choroidal neovascular lesion, respectively. In mfERG data averaging allows compensation for poor signal-to-noise ratios, but determines a loss of the spatial specificity of the mfERG.…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting mfERG data were reported in other studies and suggested that AMD interrupted delicate intraretinal mechanisms. The progression of the disease associated or not with the adverse effects of anti-VEGF could interfere with neuroretinal functions (28) . We observed a reduction in the electrical activity of the central macular region (R1) after the initiation of treatment in patients undergoing anti-angiogenic therapy with ranibizumab.…”
Section: Discussionmentioning
confidence: 99%